LEGAL CONTENT OF THE CONSUMER PROTECTION FUNCTION OF THE COMPETITION AUTHORITY OF ARMENIA - Markosyan, Tigran; Paronyan, Nare (State and Law, 2024)
Effective protection of consumers’ interests traditionally requires special attention from the state because they are “the weak party” in contractual relations with manufacturers and intermediaries. On the other hand, in the modern world, consumer protection challenges often transcend national borders, especially given the current tendencies in the growth of global e-commerce. This necessitates that states implement and continuously develop internationally recognized high standards for consumer protection. From this perspective, a cornerstone for the Republic of Armenia is the Comprehensive and Enhanced Partnership Agreement signed in 2017 with the European Union. Through this agreement, Armenia committed to aligning its consumer protection system with EU standards. At the same time, a significant role is assigned to the Competition Protection Commission in this context. Drawing from theoretical sources, national and foreign legislation, and judicial practice, this work briefly presents the history of consumer protection. It defines the concept of “consumer” within the context of competition law in the Republic of Armenia, explains the relationship between consumer interests and the competitive environment, analyzes the peculiarities of consumer protection by the Competition Protection Commission, identifies existing problems of the sphere and proposes solutions to overcome them. In the article, the authors present several scientific and practical conclusions that may be crucial for the further development of legislation and law enforcement practices.